2005
DOI: 10.1007/s00167-004-0598-1
|View full text |Cite
|
Sign up to set email alerts
|

Symptomatic calcification of the medial collateral ligament of the knee joint: a report about five cases

Abstract: Symptomatic calcifications of the rotator cuff tendons is well-known pathologic condition. However, pathologic calcifications may involve other structures of the locomotor system as well. We report about five patients (age 52-66 years) with a painful calcification at the proximal part of the medial collateral ligament of the knee joint. All five patients presented with load-dependent pain pretending meniscus symptoms, but manual valgus stress provoked severe pain at the medial side of the knee. Conventional X-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(20 citation statements)
references
References 28 publications
(59 reference statements)
0
19
1
Order By: Relevance
“…; Hedtmann & Fett ), and pain may be a feature of mineralization within other tendons and ligaments also (Muschol et al . ; Richards et al . ; Tsujii et al .…”
Section: Consequences Of Tendon Mineralizationmentioning
confidence: 99%
“…; Hedtmann & Fett ), and pain may be a feature of mineralization within other tendons and ligaments also (Muschol et al . ; Richards et al . ; Tsujii et al .…”
Section: Consequences Of Tendon Mineralizationmentioning
confidence: 99%
“…Clinically, it is most commonly seen in the rotator cuff or the supraspinatus tendon, but calcifications involving the MCL of the knee are exceedingly rare, only having been documented thrice till date [4][5][6]. Muschol et al [4] and Wei-Chou et al [5] separately reported five cases and one case of calcific tendinitis of the MCL presented with severe pain at the proximal part of the MCL.…”
Section: Discussionmentioning
confidence: 97%
“…Muschol et al [4] and Wei-Chou et al [5] separately reported five cases and one case of calcific tendinitis of the MCL presented with severe pain at the proximal part of the MCL. Open resection reduced symptoms immediately and confirmed the diagnosis by performing a biopsy.…”
Section: Discussionmentioning
confidence: 97%
“…These are commonly seen in asymptomatic patients with remote MCL injuries who have x-rays for nonrelated issues, but can cause pain the subacute setting. 36 In the setting of chronic MCL deficiency, standing, long leg, xrays will allow assessment of limb alignment. Valgus knees with chronic MCL deficiency may need corrective osteotomies to unload MCL reconstructions.…”
Section: Radiographsmentioning
confidence: 99%